Access to and participant in ICT : catalyst in improving women's status - Carreon, Lilian Mercado (2008)
The 1990s have brought winds of change all over Asia. A century ago, the print media lorded over communication. And then, radio took its place, bringing information to the most remote areas of the continent. With technological advancement and economic growth coming to Asia in the 1980s, television became the preferred if not the universal favourite medium of most people. And now, as we approach the 21st century, advancements in new communications technology are sweeping most of Asia and influencing traditional cultures and values, and causing profound changes in how we produce, use, distribute, and communicate information.